SOFTWARE ENGINNERING - SINGH, AARTI; ANIKESH, ANANYA (IJRDO -Journal of Computer Science Engineering, 2015)
The phrase ‘software engineering’ has many meanings. One central meaning is the reliable development of dependable computer-based systems, especially those for critical applications. This is not a solved problem. Failures in software development have played a large part in many fatalities and in huge economic losses. Software is intangible, complex, and capable of being transformed by a computer. Much effort has been devoted to overcoming the difficulties due to intangibility and complexity, but too little has been devoted to exploiting the third characteristic. A processoriented view of software may lead to substantial improvements in this and other respects.t his research paper tells about benefits of software engineering application its validation its problem design etc